Legal Politics Changes to The Periodization of The Term of Office of The Village Head Based on Law Number 3 of 2024 Second Amendment to Law Number 6 of 2014 Concerning Villages - Ahmad Rizal Roby Ananta (Eduvest - Journal of Universal Studies, 2025)
This study examines the recent amendments in Law Number 3 of 2024, which revises Law Number 6 of 2014 concerning Villages, particularly regarding the extension of the village head’s term from 6 years with a maximum of 3 periods to 8 years with a maximum of 2 periods. The change, influenced by demands from village heads, has sparked significant debate due to the lack of clear legal justification supporting it. This research aims to assess the rationale behind this change and its potential implications on village governance, particularly its effects on leadership effectiveness, power concentration, and community impact. Using both a statute approach to analyze the legal texts and a conceptual approach to explore the broader political and governance implications, the study finds that while the extended tenure may offer continuity and more time for village heads to implement their programs, it also raises concerns about political dynasties and potential misuse of power. The study suggests that although longer terms may improve governance, careful consideration is needed to balance this with democratic values. The findings provide crucial insights for policymakers, underscoring the potential risks and benefits of this legal reform in strengthening or weakening local democratic processes and governance.